The utilization of spent rice mash as starter culture for rice wine fermentation - Olano, Jean Mabelle O.; Azanza, Ma. Patricia V. (2001., 2001)
The study aimed to test the efficiency of using spent rice mash as starter culture in the production of rice wine. Tapuy produced from spent rice mash was not significantly different (α=0.05) from the wine produced using bubod as microbial inoculant except for the sensory parameters of bitterness in taste and aftertaste and sourness in aroma. These differences in sensory parameters were explained in the physico-chemical variations between the wine using bubod in the first level fermentation and the wine produced from spent rice mash in the second level fermentation. There was an increase in tritable acidity and soluble solids from the first level to the second level of fermentation. A decrease in wine volume yield and an increase in pH were also observed for the wines from the successive fermentation. There was no change in total alcohol content of the wine for both levels of fermentation. Total plate count of the wines produced using bubod and spent rice mash ranged from 〖10〗^5 to 〖10〗^7 cfu/ml. Changes in wine characteristics in terms of physico-chemical and sensory parameters were attributed to the possible change of microbila profile of the inoculats from bubod to spent rice mash used. The spent rice mash was hypothesized to contain more variable lactics than what was contained in the traditional bubod. Furthermore, yeast profile may have also changed. Saccharifying yeast contained in the spent rice mash was supposed to be less than that of bubod. The study recommended that rice wine from spent rice mash be considered in the production of distilled rice wine. This would try to eliminate characteristic sourness and the high turbidity that occurs in the wine from spent rice mash.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Rice wines; Fermentation